An Analysis of Students’ Errors in Translating Recount Text at The Tenth Grade of SMKN 5 Padang - Elda Martha Suri (Fakultas Sastra Universitas Ekasakti, 2023)
The problems of students' blunders in translating narrative text sparked this study. This study was carried out at SMKN 5 Padang during the 2021/2022 academic year. Many pupils struggle to translate effectively in classroom teaching and learning activities. The descriptive qualitative method was employed in this study. The sample of the population in this study was 34 students, the population was students in the tenth grade second semester of SMK 5 Padang, and the researcher took samples in the X Teknik Instalasi Tenaga Listrik 1. which comprised of 34 students using cluster random sampling. A recall text was translated as an instrument in this study. The researcher discovered five sorts of errors produced by students in translating English narrative text into Indonesian language based on data received from a test given to students. There are five types of errors: omission errors, blend errors, addition errors, misformation errors, and misordering errors.